HUBUNGAN SPASIAL ANTARA C-ORGANIK DAN TUTUPAN LAHAN DI LANSKAP DATARAN ALUVIAL TROPIKA LEMBAB KALIMANTAN TIMUR - Setianingsih, Titin Eka; Prasetyo, Rahadian Adi; Suryana; Romadhan, Panji; Nugroho, Bagus Adi (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2025)
Alluvial soils play an important role in lowland ecosystems and agriculture due to their capacity to store organic carbon. This study aimed to analyze land cover characteristics and spatial relationships between C-organic and land cover changes in the humid tropical alluvial landscape of East Kalimantan. The methods used in this study included spatial and statistical analyses to determine the relationship between C-organic and land cover. The results showed that land cover in the study area consisted of several main classes, dominated by Shrubland (29.56%), Mixed Dryland Agriculture and Shrubs (24.51%), and Plantation Areas (23.12%). The analysis of C-organic content revealed variation across different land cover types, with open land showing the highest C-organic content (2.30%). Pearson correlation analysis indicated a moderate negative correlation between C-organic and Shrubland(r = 0,4; p = 0,001), and a strong positive correlation between C-organic and plantation forests (r = 0,9; p = 0,001), suggesting that land cover changes due to anthropogenic activities can affect soil C-organic content. This study indicates that land cover dynamics contribute to changes in soil C-organic content.